Effect of Lmo7 on proliferation, migration and osteogenic differentiation of MC3T3-E1 cells in vitro - MAO Jiayi; WANG Zuolin (Kouqiang hemian waike zazhi)
[Objective:] To investigate the effects of Lmo7 gene in the process of proliferation, migration and osteogenic differentiation of MC3T3-E1 cells. [Methods:] The preosteoblasts MC3T3-E1 cells were cultured in vitro with osteogenic induction. The relative expression of Lmo7 was detected by real-time quantitative polymerase chain reaction (RT-qPCR) and Western blotting at 0, 3, 7 and 14 d respectively. At the same time, MC3T3-E1 cells were transfected with pLV-shLmo7 and pLV-shControl to construct the stably interfering cell line. Cell proliferation and cell migration were detected by CCK-8 assay, EdU assay, wound healing assay and Transwell migration assay. While alkaline phosphatase (ALP) staining was used to detect the expression activity of ALP, and RT-qPCR was used to detect the expression of osteogenesis-related genes such as Runt-related transcription factor 2 (Runx2), Osterix, alkaline phosphatase (ALP) and osteocalcin (OCN). [Results:] Lmo7 gene expression level was up-regulated during the osteogenic differentiation of MC3T3-E1 cells in vitro. The stable MC3T3-E1 cell line with Lmo7 interference was successfully constructed, and its proliferation activity was significantly improved, while its migration ability was inhibited. After osteogenic induction, compared with the control group, the ALP staining of the Lmo7 interfering cells was lighter, and the expression levels of osteogenesis-related genes such as Runx2, Osterix, ALP, and OCN were significantly down-regulated (P<0.05). [Conclusion:] Lmo7 interference promoted the cell proliferation but inhibited the cell migration. Furthermore, the osteogenic differentiation ability of cells was suppressed.